End-View Image Processing Based Angle Alignment Techniques for Specialty Optical Fibers - Li Shen; Lin Gan; Zhuoran Dong; Borui Li; Deming Liu; Songnian Fu; Weijun Tong; Ming Tang (IEEE Photonics Journal)
We propose two end-view-based digital image processing algorithms for high-precision rotational angle alignment of specialty optical fibers. The first technique is based on the cross-correlation calculation between images of two fiber ends. Accurate alignment can be achieved between identical specialty optical fibers with arbitrary end face structures. The other one is based on the self-correlation method. Two fibers with different refractive index profiles in the fusion splicer can be rotated to preset angles independently with high precision. Accurate angle alignment of less than 0.5° uncertainty and low average splicing loss for seven-core multicore fibers have been achieved in experiment. To speed up the alignment process, we further proposed two simplified algorithms for the above-mentioned techniques. Time consumption can be reduced by about 50% with acceptable alignment accuracy. We confirmed that all the methods are suitable for other kinds of specialty optical fibers, such as polarization maintaining fibers and photonic crystal fibers.